Pharmacological activities and their relationship with the oxidative stress of Morinda Citrifolia L. (Rubiaceae): an integrative review (Research, Society and Development, 2021)
The present work made an analysis of pharmacological studies of Morinda citrifolia L. and the role of oxidative stress. The research was carried out on the Capes and PubMed Journals Portal. Initially, titles, abstracts were read and those that had no relation to the topic and in duplicate were excluded. After this process, the works were read in full and the information was extracted. A total of 517 articles were found, after reading the titles and abstracts, 39 articles were selected and at the end 28 were included. Regarding the activities evaluated, 9 articles evaluated the antioxidant and anti-inflammatory activity; 5 antitumor and cytotoxicity; 3 antimicrobials; 3 antileishmania; and 8 articles that researched about different activities. According to the studies analyzed, this species has anti-inflammatory, hypotensive potential, prevention of pancreatitis, hepatoprotective and cytoprotective, and such activities seem to be related to the presence of metabolites with antioxidant activity. The antitumor activity may be related to the oxidizing activity of anthraquinones. The role of oxidative stress in the hypoglycemic and anti-obesity effects of the species still needs to be further investigated. In summary, most of the biological activities attributed to M. citrifolia can be related to the presence of compounds with antioxidant potential.